MESSAGE OF THE EDITOR-IN-CHIEF TO THE READERS OF THE SPRING ISSUE OF THE BAIKAL MEDICAL JOURNAL - Igor Vladimirovich Malov (Байкальский медицинский журнал)
Dear readers of the “Baikal Medical Journal”!We present to your attention the spring issue of the Baikal Medical Journal, in which we have collected the most interesting scientific materials.